Effect of Cognitive Control on Age-Related Positivity Effects in Attentional Processing – Evidence From an Event-Related Brain Potential Study - Liu, Haining; Liu, Yanli; Dong, Xianling; Liu, Haihong; Han, Buxin (Frontiers in psychology, 2021)
Studies investigating age-related positivity effects during facial emotion processing have yielded contradictory results. The present study aimed to elucidate the mechanisms of cognitive control during attentional processing of emotional faces among older adults. We used go/no-go detection tasks combined with event-related potentials and source localization to examine the effects of response inhibition on age-related positivity effects. Data were obtained from 23 older and 23 younger healthy participants. Behavioral results showed that the discriminability index ( d ') of older adults on fear trials was significantly greater than that of younger adults [ t (44)=2.37, p =0.024, Cohen’s d =0.70], whereas an opposite pattern was found in happy trials [ t (44)=2.56, p =0.014, Cohen’s d =0.75]. The electroencephalography results on the amplitude of the N170 at the left electrode positions showed that the fear-neutral face pairs were larger than the happy-neutral ones for the younger adults [ t (22)=2.32, p =0.030, Cohen’s d =0.48]; the older group’s right hemisphere presented similar tendency, although the results were not statistically significant [ t (22)=1.97, p =0.061, Cohen’s d =0.41]. Further, the brain activity of the two hemispheres in older adults showed asymmetrical decrement. Our study demonstrated that the age-related “positivity effect” was not observed owing to the depletion of available cognitive resources at the early attentional stage. Moreover, bilateral activation of the two hemispheres may be important signals of normal aging.